Implementation of Art Learning to Increase the Interest and Talent of Visually Impaired Students SLB Beringin Bhakti Talun, Cirebon Regency - Tesalonika Rouli Hutagaol; Citra Patricia; Suciningsasi (CV. Akademi Merdeka, 2025)
This study examines the implementation of art learning to improve the interests and talents of blind students at SLB A Beringin Bhakti, Cirebon City. Through a qualitative approach, data were collected through observations and interviews with students and teachers. Observations on May 31, 2024 showed that this school uses art learning through subjects, extracurricular activities, exercises, and competitions. Teachers have an important role in guiding students to participate in competitions up to the national level. The results of the study showed that creative and interactive art learning can improve students' motivation and art skills, such as playing musical instruments and recognizing musical instruments through touch. This program also has a positive impact on the development of the potential of blind students. With the right approach, art education becomes an effective forum for optimizing students' talents and interests, providing valuable provisions for their future.